Techniques of mesh fixation in laparoscopic ventral hernia repair: the surgical enigma - a review - Kumar, Jitendra; Raina, Rajni (International Surgery Journal, 2016)
Fixation of mesh in laparoscopic ventral hernia repair is most important step of surgery. But till date, we have not been able to reach on an any universal consensus in respect of finding any gold standard or at least so called, one ideal technique of mesh fixation. Aim of this study is to find out best or at least most appropriate technique of mesh fixation if any, on the basis of thoroughgoing of all the related literature available on line. An extensive search of literature was performed using online search engines like Google, PubMed etc. In an attempt to find all the available method of fixation technique and reports in terms of their efficacy and surgical outcome, all the related studies from the inception of laparoscopic ventral hernia surgery have been analyzed. Among all the articles we analyzed, maximum number [two RCT’s, three review’s article, four case series/retrospective studies, one prospective study of large case series, one animal study] reported in direct favors of trans fascial suture. Four reports [one RCT, one case control study, one case series and one review article] found to be having result in direct favour of tacker fixation of mesh in laparoscopic ventral hernia repair. Two other reports find no difference in Sutures and Tack.  On the basis of our result, among all the techniques of mesh fixation available today, trans fascial suturing technique of mesh fixation seems to be the best. Main drawback with this is consumption of more operating time.